Prostate cancer-associated mutation in SPOP impairs its ability to target Cdc20 for poly-ubiquitination and degradation. (28th January 2017) - Wu, Fei; Dai, Xiangpeng; Gan, Wenjian; Wan, Lixin; Li, Min; Mitsiades, Nicholas; Wei, Wenyi; Ding, Qiang; Zhang, Jinfang
Abstract: Recent studies revealed that mutations in SPOP (Speckle-type POZ protein) occur in up to 15% of patients with prostate cancer. However, the physiological role of SPOP in regulating prostate tumorigenesis remains elusive. Here, we identified the Cdc20 oncoprotein as a novel ubiquitin substrate of SPOP. As such, pharmacological inhibition of Cullin-based E3 ligases by MLN4924 could stabilize endogenous Cdc20 in cells. Furthermore, we found that Cullin 3, and, to a less extent, Cullin 1, specifically interacted with Cdc20. Depletion of Cullin 3, but not Cullin 1, could upregulate the abudance of Cdc20 largely via prolonging Cdc20 half-life. Moreover, SPOP, the adaptor protein of Cullin 3 family E3 ligase, specifically interacted with Cdc20, and promoted the poly-ubiquitination and subsequent degradation of Cdc20 in a degron-dependent manner. Importantly, prostate cancer-derived SPOP mutants failed to interact with Cdc20 to promote its degradation. As a result, SPOP -deficient prostate cancer cells with elevated Cdc20 expression became resistant to a pharmacological Cdc20 inhibitor. Therefore, our results revealed a novel role of SPOP in tumorigenesis in part by promoting the degradation of the Cdc20 oncoprotein. Highlights: Cullin 3 negatively regulates Cdc20 stability in prostate cancer. SPOP promotes Cdc20 poly-ubiquitination and degradation. Prostate cancer-associated mutants are defective in interaction with Cdc20. SPOP -deficient prostate cancer cells become resistant to Cdc20 inhibitor.